Statistical studies in genetic toxicology: a perspective from the U.S. National Toxicology Program. - Margolin, B H (1985)
This paper surveys recent, as yet unpublished, statistical studies arising from research in genetic toxicology within the U.S. National Toxicology Program (NTP). These studies all involve analyses of data from Ames Salmonella/microsome mutagenicity tests, but the statistical methodologies are broadly applicable. Three issues are addressed: First, what is a tenable sampling model for Ames test data, and how does one best test the adequacy of the Poisson sampling assumption? Second, given that nonmonotone dose-response curves are fairly common in the Salmonella assay, what new statistical techniques or modifications of existing ones seem appropriate to accommodate to this reality? Finally, an intriguing question: How can the extensive NTP Ames test data base be used to assess the characteristics of any mutagen-nonmutagen decision rule? The last issue is illustrated with the commonly used "two-times background" rule.